VD_FINDINFO HC / 2011 / 467 vom 10. August 2011 - VD Tribunal cantonal (2011)
DIVORCE, MESURE PROVISIONNELLE, DROIT DE GARDE, DÉMÉNAGEMENT | 137 al. 2 CC, 176 al. 3 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 308 CPC (CH), 310 CPC (CH)